2015
DOI: 10.1016/j.ijid.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the association between meteorological factors and hand, foot, and mouth disease using spatial panel data models

Abstract: Spatial panel data models are useful when longitudinal data with multiple units are available and spatial autocorrelation exists. The association found between HFMD and meteorological factors makes a contribution towards advancing knowledge with respect to the causality of HFMD and has policy implications for HFMD prevention and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 25 publications
9
50
1
Order By: Relevance
“…In Hong Kong, temperature and precipitation were also found to play important roles based on a regression model [9]. A study in Jinan of northern China also found that average temperature and average relative humidity were positive associated with HFMD, while precipitation and sunshine hours were negatively associated [17]. In South Korea, the risk of HFMD has been shown to increase with the rise of temperature and relative humidity [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hong Kong, temperature and precipitation were also found to play important roles based on a regression model [9]. A study in Jinan of northern China also found that average temperature and average relative humidity were positive associated with HFMD, while precipitation and sunshine hours were negatively associated [17]. In South Korea, the risk of HFMD has been shown to increase with the rise of temperature and relative humidity [20].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies focused on the influence of various factors on HFMD [2,7,11,12,13,16,17,18,19,20,21,22,23,24], and a number of potential risk factors were analyzed in this study. Risk factors relating to socioeconomic variables were collected, including population density, gross domestic product (GDP) per capita of each county, and the proportion of primary/tertiary industry in the study area (Figure 2, Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Many published research papers reported that climatic factors including humidity, temperature, wind speed and rainfall amount are major contributors to the distribution of HFMD [9][10][11]. Northern Thailand has three seasons; raining, hot (summer), and cold (autumn).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies had illustrated the association between social-ecological factors, including temperature, rainfall, wind speed, relative humidity, and HFMD (Liao et al 2015;Liu et al 2015a;Wang et al 2015b). The impact of socialecological factors across secondary administrative unit areas is a challenging issue due to the spatial effects.…”
Section: Introductionmentioning
confidence: 99%